Analisis Karakteristik Hidrogeokimia Airtanah Di Pulau Koral Panggal, Kepulauan Seribu, DKI Jakarta - Ahmad Cahyadi; Wahyu Hidayat (JURNAL GEOGRAFI, 2017)
The small island has a very unique hydrological characteristics. The unique character are low rainfall, rain catchment narrow and high vulnerability to seawater intrusion. This study aims to (1) analyze the groundwater hydrogeochemistry facies in Panggang Cay and (2) to analyze the evolution of groundwater hydrogeochemistry in Panggang Cay. Data used include major element analysis results of the groundwater samples taken from the study site. Hidrogeochemistry fasies of groundwater determined the type of diagram analysis stiff, while the analysis of the hydrogeochemistry evolution of groundater analyzed using piper diagram. Groundwater hydrochemical facies in Panggang Cay is MgCl2 with hydrogeochemical evolution of CaCO3 into MgCl2. The evolution of hydrogeochemistry fasies that occur indicate the sea water intrusion process.